Promoting Curriculum and Learning System at Mixed Islamic Boarding Schools: A Literature Review - Herniawati, Ani; Basri, Hasan; Suhartini, Andewi (International Journal Corner of Educational Research, 2025)
Islamic boarding schools are Islamic educational institutions that play an important role in instilling the noble characters in Indonesian society. This study aims to identify the curriculum of mixed Islamic boarding schools, learning systems, advantages of mixed Islamic boarding schools, challenges of mixed Islamic boarding schools, and the implications of mixed Islamic boarding schools for the development of Islamic education. In this study, the researchers employ a qualitative approach under the library research method. The results of this study assert that the curriculum used by mixed Islamic boarding schools is in the form of an integrated curriculum which integrates the Islamic curriculum and the general curriculum. Furthermore, through the integrated curriculum and learning system, the mixed Islamic boarding schools have various advantages, i.e: the balance of Islamic and general knowledge; technology mastery; having noble characters; relevance to the challenges of the era; and social and cultural adaptation. In addition, the challenges faced today are: maintaining a balance between tradition and modernity of Islamic boarding schools; maintaining the quality of educators; improving the quality and quantity of Islamic boarding school facilities and infrastructure; and financing Islamic boarding schools. Finally, the implications of mixed Islamic boarding schools are on the development of Islamic education include: maintaining an adaptive Islamic education model, maintaining and improving the quality of output and outcome, contributing to nation building, maintaining and preserving Islamic boarding schools’ traditions, and safeguarding Islamic science.